PENGARUH GREEN MARKETING KEBIJAKAN KANTONG PLASTIK BERBAYAR TERHADAP GREEN BEHAVIOUR MASYARAKAT KOTA BOGOR - Novianti, Ayi Indah; Kartika, Lindawati (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
Paid plastic bags policy issued by The Ministry of Environmental and Forestry to reduce plastic waste problem and promote green behaviour lifestyle. In order to change consumer behaviour when using plastic bags, government need to look over the marketing of paid plastic bags policy. The objective of this study are to identify customer respons about using their own bags, customer perceptions of green marketing and green behaviour, analyze green marketing of paid plastic bags policy influence towards green behavior.Primary data are obtained by questionnaire method and the secondary data are obtained from Department of Industry and Trade. The data have been analyzed using structural equation model and descriptive analysis. The result of this study shows after the policy applied, more customers are willing to carry their own shopping bag and reduce using plastic bags. The price of plastic bags are still considered too cheap and should be increased. Green marketing process that has significance influence towarads green behavior are know your customer, empowering customer and reassure the buyer. Keywords: green marketing, green behavior